Transnational Immigrant Narratives on Arab Democracy - Fakhoury, Tamirace (2014)
This article analyses the discourse of Arab transnational student associations at the University of California in Berkeley (UCB) on Arab democratization. It places focus on their narratives during the 2011 uprisings. Its findings, based on interviews and qualitative data, show that these student associations craft a discursive and broader conception of Arab democracy not confined to suffrage and institutions, and extending beyond the borders of the Arab world. They further draw on various indirect mechanisms in their host land to convey their discourses and impact homeland democratization. Still, their agency remains constrained by several structural factors.